2004
DOI: 10.1071/mf03080
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Symbiodinium from bleached Australian scleractinian corals (Acropora hyacinthus, Favites complanata and Porites solida)

Abstract: Coral bleaching results from the dissociation of Symbiodinium and is primarily related to sea surface temperatures above mean yearly maximums. The numbers of live, dead, and mitotic Symbiodinium cells lost from three scleractinian corals from three different families (Acropora hyacinthus, Favites complanata, and Porites solida), which have not been studied previously in central Queensland (Australia), were compared at 28, 30, 32, and 34°C. Specific expulsion rates, growth rates, and mitotic indices were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…Bhagooli and Hidaka (2002) found that the intracellular MI of zooxanthellae within the coral Galaxea fasicularis increased with temperature, and was maximal at the observed bleaching threshold temperature of 30 • C. The authors concluded that, "the host appeared to lose the capacity of controlling algal cell division after 7-day exposure to 30 • C". A positive association between rising temperature, zooxanthellae MI, and coral bleaching was also recorded by Strychar et al (2004) for three different coral families (Acropora hyacinthus, Favites complanata and Porites solida). Porites solida (massive morphology) was the most thermally tolerant coral, A. hyacinthus (branching/plate morphology) bleached most readily at low temperatures, and F. Complanata (mounding morphology) showed intermediate bleaching tolerance to elevated temperature (Fig.…”
Section: The Coral-algae Symbiosis: Thermal Tolerance Coupled To Zooxmentioning
confidence: 70%
See 3 more Smart Citations
“…Bhagooli and Hidaka (2002) found that the intracellular MI of zooxanthellae within the coral Galaxea fasicularis increased with temperature, and was maximal at the observed bleaching threshold temperature of 30 • C. The authors concluded that, "the host appeared to lose the capacity of controlling algal cell division after 7-day exposure to 30 • C". A positive association between rising temperature, zooxanthellae MI, and coral bleaching was also recorded by Strychar et al (2004) for three different coral families (Acropora hyacinthus, Favites complanata and Porites solida). Porites solida (massive morphology) was the most thermally tolerant coral, A. hyacinthus (branching/plate morphology) bleached most readily at low temperatures, and F. Complanata (mounding morphology) showed intermediate bleaching tolerance to elevated temperature (Fig.…”
Section: The Coral-algae Symbiosis: Thermal Tolerance Coupled To Zooxmentioning
confidence: 70%
“…5a), with the different zooxanthellae types varying in terms of thermal growth optimum (Sakami, 2000;Kinzie et al, 2001;Strychar et al, 2004). Significantly, the thermal growth optimum for many of the zooxanthellae types that associate with corals often exceeds the thermal break-point of the symbiotic association (> 32 • C) (see e.g.…”
Section: The Enhanced Respiratory (R) Cost Resulting From a Large Nummentioning
confidence: 99%
See 2 more Smart Citations
“…All artificial marine water was twice exposed to a sock filter (filter bag, 200 µm) before use in experimental analyses to ensure dissolution of salt in the water. Ambient lighting was simulated by a 12 h light : 12 h dark diel cycle (Mobley and Gleason, 2003) with two Super Actinic bulbs and two Actinic white bulbs following Strychar et al (2004).…”
Section: Introductionmentioning
confidence: 99%